Importance of ict in the teaching-learning process: middle and higer educaction studies (2019)
The integration of ICT in education entails several challenges: the first, to diagnose, at a global level, how this process is being carried out in different educational fields. Likewise, another challenge is to analyze what has really been the impact that this integration has had on improving educational quality in Colombia. It is assumed that ICT applied to education generates successful paths to promote both teaching and learning. However, it is necessary to enter the fields of education to corroborate if the previous statement is valid. A third challenge would be to analyze the effect of ICT on the efficiency of educational institutions. In this sense, it is not only necessary to determine the ICT integration process, but also to determine how the same institutions assume responsibility for the digital transformation of education. Another challenge is to validate, experiences carried out using ICT to improve learning processes. Finally, another of the challenges that can be highlighted, and is the most relevant, is the need to assume an ethical stance regarding the management of ICT in education. This book covers each of the challenges with the aim of promoting the processes of innovation and digital transformation of education from a scientific, critical, and above all, ethical perspective.